Pearl without Oyster; Pregnancy without Uterus! - Rose, Delphine T.; R., Rajarajeswari (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Is pregnancy possible after removal of the uterus? Pregnancy is virtually never thought of after hysterectomy. Although rare it is still possible for a reproductive age group woman to conceive after hysterectomy when the tubes and ovaries are left behind. A sperm enter through a fistulous tract in the vaginal vault, fertilize the ovum, implant in the tube and grow. The end result can be catastrophic, if diagnosed late. Fortunately such post-hysterectomy ruptured ectopic gestation is a very rare event; so far only 72 cases have been reported in literature. Here we report a case of ruptured tubal gestation in a 25year old patient after four years of peripartum hysterectomy, who had a successful outcome because of timely diagnosis and early treatment.